Modeling of cost control systems for decision support in the management of the electric grid company - A. M. Kumaritov; A. E. Dzgoev; O. R. Babochiev; I. M. Huzmiev (Известия высших учебных заведений: Проблемы энергетики)
Using the experiment design method an useful adequate model connecting the financial expenditure on data transference in terms of the electric energy consumption with the counting amount of various measuring devices was developed. The categories of the measuring devices registrating the energy expenditure were determined and the category having the greatest dependence of expenditure on the counting amount was revealed.